Work-related psychopathology: Rates in different work activities and relationship between subjective perception of work distress and psychiatric disturbances. - Nolfe, Giovanni; Mancini, Paola; Mancusi, Riccardo; Zontini, Gemma; Nolfe, Giuseppe (Work, 2014)
BACKGROUND: The link between work distress and negative mental health outcome is an emergent topic in the scientific literature. The studies that evaluated the risk of work-related psychopathologies in the different job sectors have obtained so far controversial and inconclusive results. The identification, by means of standardized evaluation tools, of the work activities at higher risk of poor mental health is a relevant target for the occupational psychiatry and medicine. OBJECTIVE: To evaluate the relationship between the psychosocial work conditions and work related psychiatric disturbances and to verify the relationship between the higher pathogenic effect of work and specific job activities. PARTICIPANTS: A six-month diagnostic trial was conducted on 234 patients (35.4% women and 64.6% men). METHODS: Psychiatric diagnoses were according to DSM-IV criteria; anxious and depressive dimensions were studied by means of Hamilton-Anxiety-Scale and Hamilton Scale for Depression; psychosocial work environments and bio-psycho-social features were measured by Naples-Questionnaire of Work Distress. Groups with higher and lower work-related pathogenesis were compared and their distribution among specific job activities was evaluated. RESULTS: Mood disorders were strongly linked to negative work environment. Patients with severe bullying obtained higher scores on Hamilton-Anxiety-Scale and Hamilton Scale for Depression than those with lower work-pathogenesis. The highest scores on Naples-Questionnaire of Work Distress were related to mood disorders, to poorer bio-psycho-social functioning and to higher work etiology. No significant relationship between work activities and work-related psychopathologies was found. CONCLUSION: Workplace bullying is predictive of work-related psychiatric disturbances with more severe clinical features and bio-psycho-social consequences. No significant differences were found about the relationship between work-related psychopathologies and work activities.